Internet Use Related to Suicidal Thoughts and Help-Seeking – Preliminary Results of a Study with Depressive Patients - V. Voros; Z. Szabo; E. Torma; A. Nagy; J. Fekete; T. Tényi; S. Fekete; P. Osvath (European Psychiatry, 2022)
Introduction Suicide-related Internet use is becoming more common, and many research study its potential risks and benefits.